Mental Health Status of Teachers During the Second Wave of the COVID-19 Pandemic: A Web-Based Study in Bangladesh - Hossain, Md. Tanvir; Islam, Md. Akhtarul; Jahan, Nusrat; Nahar, Mst. Tanmin; Sarker, Md. Juwel Ahmed; Rahman, Md. Mostafizur; Deeba, Farah; Hoque, Kazi Enamul; Aktar, Rina; Islam, Md. Mazharul; Hossain, Mohammed Zaber; Siddiqua, Laila; et al. (Frontiers in Psychiatry, 2022)
Background: Following the outbreak of the COVID-19 pandemic, the government of Bangladesh implemented strict non-therapeutic measures, i.e., ‘social distancing,’ ‘lockdown,’ ‘work from home,’ in the first quarter of 2020. Like other professionals, teachers at schools, colleges and universities were confined within households. However, the introduction of online education imposed an additional burden on teachers along with growing household responsibilities, thus, affecting their psychological state. Aims: This study was aimed to explore the prevalence of mental health problems among teachers in Bangladesh and to identify the associated risk factors. Methods: This web-based cross-sectional study was conducted during the second wave of COVID-19 pandemic in Bangladesh. Data were collected from 381 teachers working at schools, colleges, and universities between 01 August to 29 August 2021 by administering a self-reported e-questionnaire using Google Form, where the mental health of teachers was assessed by the Depression, anxiety, and stress scale 21 (DASS 21). Data were analyzed using IBM SPSS Statistics (Version 26) and STATA Version 16, and multiple linear regression was executed to predict mental health problems among teachers. Results: The findings indicate that the overall prevalence of depression, anxiety, and stress among teachers was 35.4%, 43.7%, and 6.6%, respectively. The prevalence was higher among male and older teachers than among their female and younger colleagues. The findings further showed that place of residence, institution, self-reported health, usage of social and electronic media, and fear of COVID-19 significantly influenced the mental health status of teachers. Conclusion: It is strongly recommended that the government and policymakers provide proper mental health services to teachers in order to reduce mental health problems and thus sustain the quality of education during and after the pandemic.